Crossing over the stories behind the stories - Edward, John (New York : Princess Books ; Carlsbad, CA : Distributed by Hay House, 2003)
John Edward, renowned psychic medium and television host of Sci-Fi Channel's Crossing Over, shares amazing stories of the people and spirits he has encountered throughout his life.
Subtitle from container.
Read by the author.
Keywords: Edward, John; Mediums -- United States